Ameliorative Effect of Carica papaya Seed Extract on Diabetic Rat Model with Muscle Atrophy - Devyani Diah Wulansari; Devyana Dyah Wulandari; Reine Risa Risthanti; Aguslina Kirtishanti (Fakultas Farmasi, Universitas Surabaya, 2019)
This study aims to prove that papaya seed extract has the potential to improve muscle cell atrophy in diabetic conditions. Type 2 diabetes mellitus (DM) animal model were made with conditions similar to type 2 DM in humans i.e. with long-term (56 days) high sugar (fructose) consumption. Then, the next 14 days were treated with papaya seed extract at the dose of 100, 200, and 300 mg/kg BW orally. Body weight and blood glucose levels were monitored throughout the study period. At the end of the study, histopathological examination of gastrocnemius skeletal muscle tissue was carried out using hematoxylin-eosin staining and measuring myocyte cell area. Results showed that there is a correlation between blood glucose levels with the area of muscle cells which explains that the decrease in blood glucose levels is in line with the increase in the area of muscle fiber cells. In the diabetic group and the treatment group the dose of 100 mg/kg BW has a smaller area, whereas in the treatment group the dose of 200 and 300 mg/kg BW has an area close to the area of the muscle cell in the normal group. This is supported by the results of measurements of the area of muscle fiber cells observed through cross sections and measured at the end of this study. The treatment group at the dose of 200 and 300 mg/kg BW did not have significant difference (P>0.05) compared to the normal group. It can be concluded that papaya seed extract therapy at the dose of 200 and 300 mg/kg BW on diabetic rats can reduce the fasting blood glucose levels so that it can ameliorate cell atrophy in the diabetic conditions.